Migration, Cultural Adaptation, and Work: Haitians in Mato Grosso do Sul - da Silva Cruz, Wydglan; José de Souza Peres, Alexandre; Pinho de Almeida , Luciane (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
This study aimed to investigate factors related to the cultural adaptation and employment experiences of Haitian migrants in the Brazilian labor market, specifically in the state of Mato Grosso do Sul. To do so, everyday situations of migrants in the municipality of Três Lagoas were examined. Data were collected through semi-structured interviews with eight male migrants aged 18 and older. The interviews were transcribed, and the textual data were organized and imported into the IRaMuTeq software (Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires), through which they were analyzed. The following analyses were conducted: Descendant Hierarchical Classification and Similarity Analysis. The analyses resulted in seven word classes highlighting aspects of cultural adaptation to the work models prevalent in the region, including the roles performed at work, cultural differences between the home country and the new place of residence and work, language difficulties, and the challenges of facing prejudice, racial discrimination, and xenophobia both at work and in other contexts, among other points. Haitian migration in Brazil is relatively recent and underexplored. It is expected that the results presented here will contribute to research on this phenomenon by complementing qualitative studies with samples from other Brazilian regions, as well as providing insights for the design of studies (e.g., surveys) with more robust samples, thus facilitating a broader and more comprehensive understanding of the cultural adaptation and employment experiences of these migrants.